Analysis of Mudharabah Financing Accounting Treatment at Bank Mandiri Syariah Banda Aceh Branch - Fajri Salimi; Agustina Agustina; Iswandi Idris (Enrichment : Journal of Management, 2021)
The tasks of Islāmic banks not perceive the idea of premium on cash and don't perceive getting cash, yet what exists is a mudharabah association/coöperation with the rule of benefit sharing, while at the same time acquiring cash is an option exclusively for social purposes with next to no pay. So that in its activity a few Islāmic bank items are known, incorporating items with the mudharabah guideline. The arrangements on mudharabah bookkeeping in the Assertion of Monetary Bookkeeping Norms (PSAK) No. 105. Bank Mandiri Branch Office in Aceh Changed over to Bank Syariah Mandiri, the transformation strategy connect by the Bank Mandiri Gathering to help execution of Qanun No. 11/2018 with regards to Islāmic Monetary Organizations in Aceh Region. The particular motivation behind this review was to dissect the act of Monetary Bookkeeping Guidelines (SAK) number 105 about mudharabah financing in the current financing framework at Bank Mandiri Syariah Banda Aceh Branch. The examination strategy is subjective exploration with graphic information investigation strategies. The guidelines utilized at Bank Mandiri Syariah Banda Aceh (BSM) Branch for the most part use ways that are by and large appropriate to monetary organizations, while PSAK 105. Bank Mandiri Syariah Banda Aceh Branch in leading financing has kept the current guidelines reliably, while the record of mudharabah financing is endorsement PSAK 105 so that in completing its business it is endorsement suggest.